ALPINE BASEMENT OUTCROPS AT NORTHERN PELOPONNESUS: IMPLICATIONS FOR THE EARLY STAGES IN THE EVOLUTION OF THE CORINTH RIFT - Skourtsos, E.; Kranis, H.; Zambetakis-Lekkas, A.; Gawthorpe, R.; Leeder, M. (Bulletin of the Geological Society of Greece, 2016)
We focus on the central and eastern southern onshore parts of the Corinth Rift (CR), where basement outcrops are few and of limited extent, to study three key locations: a basement inlier east of Xylokastro, a new outcrop of the Tripolis Unit at the western edge of the Xylokastro horst, and a re-mapped and re-evaluated outcrop of the Pindos Unit northwest of Nemea. The results of this study show that there are elements which could help overcome the significant difficulties in our understanding of the structure and evolution of the rift, posed by the lack of basement outcrops in the central and eastern onshore parts of the Rift. This, in turn, calls for a reconsideration of the generally accepted idea that the broader onshore eastern sector of the CR lacks significant basement and intrabasinal faults.